2010
DOI: 10.1107/s0909049510023654
|View full text |Cite
|
Sign up to set email alerts
|

A confocal set-up for micro-XRF and XAFS experiments using diamond-anvil cells

Abstract: SynopsisA confocal setup for micro-XRF and XAFS for in-situ high-pressure and temperature experiments is presented. AbstractA confocal setup is presented that improves micro-XRF and XAFS experiments with highpressure diamond anvil cells (DAC). In this experiment, a probing volume is defined by the focus of the incoming synchrotron radiation beam and that of a polycapillary X-ray half-lens with a very long working distance, which is placed in front of the fluorescence detector. This setup enhances the quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Currently, the detection limit for HP XFS is at a few ppm level for elements down to atomic number 22 (Ti) and to a pressure of 10 GPa at high temperatures to at least 1273 K [253][254][255]. A confocal geometry has been developed for minimizing unwanted background signals [256], further improving efficiency and consequently lowering the detection limit.…”
Section: Hp X-ray Fluorescence Spectroscopymentioning
confidence: 99%
“…Currently, the detection limit for HP XFS is at a few ppm level for elements down to atomic number 22 (Ti) and to a pressure of 10 GPa at high temperatures to at least 1273 K [253][254][255]. A confocal geometry has been developed for minimizing unwanted background signals [256], further improving efficiency and consequently lowering the detection limit.…”
Section: Hp X-ray Fluorescence Spectroscopymentioning
confidence: 99%
“…This confocal setup enhances the quality of the fluorescence and XAFS spectra and, thus, the sensitivity for detecting elements at low concentrations. It efficiently suppresses signal from outside the sample chamber, which stems from elastic and inelastic scattering of the incoming beam by the diamond anvils as well as from excitation of fluorescence from the body of the diamondanvil cell (Wilke et al 2010). …”
Section: Experimental Design Of Confocal Xafsmentioning
confidence: 98%
“…Of course, it also enables a depth elemental profiling. There are many reports of depth elemental profiling for layered materials such as paint layers [29][30][31][32][33][34][35][36][37][38][39]. The author's research group at OCU has reported a depth elemental profile for car paint chips, which have several layers depending on the type of car and manufacturing process [40].…”
Section: Confocal Micro-xrf In the Laboratorymentioning
confidence: 99%